The relationship between gait biomechanics, selected lower extremity strength, static lower extremity measures and injury history in division II collegiate middle to long distance runners - Cannon, A.; Finn, K. E.; Medieros, B. (International Calgary Running Symposium, August 14-17, 2014, 2014)
Background: Overuse injuries among runners are common. Injury origins are confounding; they frequently result from a combination of muscle flexibility, muscle strength, biomechanical factors, and training errors. Therefore, the purpose of this study was to attempt to clarify how these factors interact between the rarely and frequently injured. Methods: Twenty collegiate, middle to long distance runners (ten males/ten females) have been recruited to participate in the study. The testing battery is a standardized injury history, running biomechanically assessed using a three-camera high-speed image capture system, strength assessment via isokinetic dynamometry of quadriceps/hamstrings, and selected lower extremity static measures. To date, we have collected data on six subjects (three females/three males) and categorized them based on injury history. Three subjects reported three or more injuries in the past twelve months (e.g. injured) and three reported two or less injuries in the same period (non-injured) Results: Preliminary results indicate that the two groups may differ. A significant difference was seen in navicular height drop (p<0.05) and trends toward significance were observed in tubercle angle (p=0.09) and standing calcaneus angle (p=0.08). Also, a significant difference (p<0.05) was observed in right to left quadriceps isokinetic peak torque at 60°s in the injured group. Lastly, significant differences (p<0.05) were seen when comparing right to left mean peak hip stance phase abduction in both groups. Conclusion: These results are quite preliminary, though trends are intriguing and possibly clinically relevant and foundational in their application to decreasing injury in middle to long distance collegiate runners.